On the identity of Clistocoeloma balansae A. Milne-Edwards, 1873, and C. tectum (Rathbun, 1914), with description of a new species from the West Pacific (Crustacea: Decapoda: Sesarmidae) - Lee, B. Y.; Ng, N. K.; Ng, Peter K.l. (Zootaxa, 2013)
The identity of the mangrove sesarmid crab Clistocoeloma balansae A. Milne-Edwards, 1873, is clarified on the basis of the types from New Caledonia, and fresh material from Vanuatu and the Philippines. Sesarma (Sesarma) tectum Rathbun, 1914, is shown to be a junior subjective synonym of C. balansae A. Milne-Edwards, 1873. A new species, C. melanesi-cum, superficially similar to C. balansae, is described from Vanuatu, New Caledonia, and, Solomon Islands.